(untitled) (Research, Society and Development, 2021)
Objective: To describe the experiences lived in the process of organizing the activities of a hemodialysis clinic to care for patients during the Covid-19 pandemic. Methodology: This is an experience report with a descriptive character of the aspects experienced by the authors in the process of organization and training of a renal replacement therapy unit in hemodialysis and nephrology, in a municipality in the central north health region of the state of Bahia, for coping with Covid-19 during the extracurricular nursing internship from March to December 2020. The Maguerez Arch Problematization methodology was applied, which allows the researcher to identify problems in the place of observation. Results: We observed that the service coordinators carefully analyzed the clinic’s care routines, at this time in order to organize the work process for coping with Covid-19, with a survey of actions that should be implemented to avoid contamination by the virus during hemodialysis sessions. Preventive measures were strictly adopted, through training with employees, patients and caregivers. The adherence of those involved showed great responsibility, proven, in this period of 230 patients, only 13% had the Covid-19. Final considerations: This experience in such a complex epidemiological context contributed significantly to the professional construction of those involved, adding the importance of seeking scientific information, practical experience and development of management skills in health services while still in graduation.